Pengembangan Media Pembelajaran Penetralisir Asap Rokok dalam Meningkatkan Hasil Belajar Siswa serta Meningkatkan Minat Belajar Siswa pada Mata Pelajaran IPA Kelas V SDN 193 Pekanbaru - Syahrul Rahmansyah (At-Tajdid : Journal of Islamic Studies, 2023)
This study aims to ascertain the viability of creative and media-rich activities on the topic of clean air for health as well as the impact of media on raising learning interest in primary children and improving learning outcomes. This study employs research and development techniques. Based on the study's findings, it is concluded that student learning outcomes analysis meets KKM by 100%, student and teacher questionnaires produce very positive results, student interest in learning receives very active categories, and the feasibility of the media as a method of neutralizing cigarette smoke has a very feasible category. An increase in student learning interest in the medium was seen based on the findings of an investigation of improved student learning outcomes.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//